2003
DOI: 10.1530/eje.0.1490511
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lipolysis during acute GH exposure increases insulin sensitivity in previously untreated GH-deficient adults

Abstract: Objective: Previous studies evaluating the lipolytic effect of GH have in general been performed in subjects on chronic GH therapy. In this study we assessed the lipolytic effect of GH in previously untreated patients and examined whether the negative effect of enhanced lipolysis on glucose metabolism could be counteracted by acute antilipolysis achieved with acipimox. Methods: Ten GH-deficient (GHD) adults participated in four experiments each, during which they received in a double-blind manner: placebo (A);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 41 publications
5
19
0
Order By: Relevance
“…GH is a well-established lipolytic hormone in both animals and humans (24,34). In healthy individuals, baseline FFA values often more than double with peak values recorded 2-3 h after a single bolus injection of GH (39).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GH is a well-established lipolytic hormone in both animals and humans (24,34). In healthy individuals, baseline FFA values often more than double with peak values recorded 2-3 h after a single bolus injection of GH (39).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, baseline FFA values often more than double with peak values recorded 2-3 h after a single bolus injection of GH (39). Under physiological conditions, GH-induced lipolysis in adipose tissue may be a major contributor to the diurnal supply of lipid fuels (29,34,35). On the other hand, conflicting data related to the roles of FGF21 on lipolysis has been reported (5,9,36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GH is a lipolytic hormone that induces elevations in free fatty acid (FFA) concentrations, and it is speculated that worsening of insulin sensitivity is a consequence of enhanced omental lipolysis, leading either to alterations in intermediate metabolism or to alterations in membrane characteristics (6,27,32). Previous work in GH-deficient adults (35,36) has shown that prevention of lipolysis by coadministration of GH with FFA regulators can partially prevent the deterioration of insulin sensitivity. This work suggested that GH-induced insulin resistance is mediated by GH-induced lypolysis and that inhibition of lipolysis may result in improved insulin sensitivity.…”
mentioning
confidence: 99%